Jak nie wpaść w Kanał (Sportowy), czyli o odpowiedzialności za bezpodstawne zgłoszenie internetowego naruszenia praw autorskich do dostawcy usług pośredniczących na tle sprawy Kanał Sportowy v. Polsat – cz. II - Mielniczuk-Skibicka, Martyna; Skibicki, Rafał (Wydawnictwo C.H. Beck, 2021)
The article is divided into two parts. In the first one, the authors discuss the basis of responsibility for unjustified reporting of copyright infringement on the grounds of Polish law. The issue is considered based on the Act of 12 July 2002 on supply of e-services, the principle of delictual liability of article 415 of civil code and the Act of 16 April 1993 on preventing unfair competition. The paper is concluded with deliberations on responsibility for infringement of personal interests. The second part is devoted to the analysis of responsibility of a person who unjustifiably reports copyright infringement on the level of EU law. The authors took into account solutions implemented in Finland, which is the only country in the EU that regulated the issue of unjustified reporting of copyright infringement to intermediary entities. Later on in the article, legal and comparative deliberations regard the U.S. law, which represents the archetype for EU regulations regarding responsibility for online copyright infringement, and regulated responsibility of a person who unjustifiably reports it. Moreover, the authors discuss implications of the changing issue resulting from new legislative projects – a draft law on protection of freedom of speech in social media and the EU regulation on digital services. Finally, there are postulates both de lege lata and de lege ferenda.
Keywords: intellectual property law; reporting law violation; hosting providers; responsibility for unjustified reporting of violation